2016
DOI: 10.1177/2156587215612626
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Antihyperlipidemic Effects of Ethanol Extract of Rosa canina L. fruit on Diabetic Rats

Abstract: Rosa canina L. (Rosaceae) has been traditionally used as a medicinal plant. This study was undertaken to evaluate the antidiabetic and antihyperlipidemic effects of Rosa canina fruit extract in streptozotocin induced diabetic rats. The results showed oral administration of Rosa canina fruit extract significantly ameliorated the high levels of blood glucose compared with the control group. Serum triglyceride levels significantly decreased by the administration of Rosa canina extract compared with control. Histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 22 publications
1
22
1
1
Order By: Relevance
“…These results were also confirmed by Taghizadeh et al (2016) who found that the administration of Rosa canina extract in STZ-induced diabetic rats at a dose of 250 mg/kg body weight significantly decreased the levels of serum triglycerides whereas serum cholesterol, low-density lipoprotein, and high-density lipoprotein levels were not modified [134]. …”
Section: Rose Hip and Diseasesupporting
confidence: 72%
See 1 more Smart Citation
“…These results were also confirmed by Taghizadeh et al (2016) who found that the administration of Rosa canina extract in STZ-induced diabetic rats at a dose of 250 mg/kg body weight significantly decreased the levels of serum triglycerides whereas serum cholesterol, low-density lipoprotein, and high-density lipoprotein levels were not modified [134]. …”
Section: Rose Hip and Diseasesupporting
confidence: 72%
“…These results were supported by Orhan et al [133], who found that R-H 2 O fraction of Rosa canina fruits reduced blood glucose level significantly in streptozotocin (STZ)-induced diabetic rats (50–62%) and demonstrated the hypoglycemic effect of Rosa canina in an animal model of diabetes mellitus. Moreover, histopathological studies of organs from STZ-induced diabetic rats revealed that low doses of Rosa canina extract (250 mg/kg body weight) significantly increased the number of islets in comparison with diabetic rats of the control group and improved the histology of necrotic islets of pancreas [134]. This effect was not associated with the phenolic content Rosa canina —which is mainly contained in ethanol and methanol extracts—but with different bioactive compounds such as vitamin B and C, carotene, organic acids, flavonoids, tannins, monosaccharides, oligosaccharides, and pectins contained in the polar extract [135].…”
Section: Rose Hip and Diseasementioning
confidence: 99%
“…Wyniki te zostały również potwierdzone przez Taghizadeha i wsp. [41], którzy wykazali, że podawanie ekstraktu z dzikiej róży szczurom z cukrzycą indukowaną streptozotacyną w dawce 250 mg/kg masy ciała znacząco obniżało poziomy triglicerydów w surowicy, podczas gdy poziom cholesterolu w surowicy pozostał bez zmian [41].…”
Section: Działanie Przeciwhiperlipidemiiunclassified
“…Therefore, the hypoglycemic activity of a number of plant extracts has been evaluated and confirmed in animal models [8][9][10]. Many recent studies have revealed that plant-based formulations can contribute to a better management of diabetes, as certain phytochemicals exert antioxidant, anti-inflammatory, and glucose-lowering effects [10][11][12][13]. In Vietnam, Adenosma bracteosum Bonati.…”
Section: Introductionmentioning
confidence: 99%